Green human resources management application to enhance environmental performance in Hotel Le Morgane, France - Ni Made Arisani Dewi; Sylvine Pickel Chevalier; Ni Nyoman Triyuni; I Gede Mudana (Politeknik Negeri Bali, 2023)
This study aimed to determine the application of green human resource management at Hotel Le Morgane, France, and to analyze the hotel's environmental performance through the application of green human resource management. The method used is descriptive statistics by distributing questionnaires to 42 employees. Data collection methods used in this study were observation, a document study, a literature study, interviews, and questionnaires. The results of study indicate that green human resources application at Hotel Le Morgane starts with Green Recruitment and Selection, Green Training and Development, Green Performance Assessment, and Green Reward and Compensation. The hotel needs to pay attention to environmental performance indicators in practices carried out by human resources.